High Compliance to an Enhanced Recovery Pathway for Patients ≥65 Years Undergoing Major Small and Large Intestinal Surgery Is Associated With Improved Postoperative Outcomes. Issue 6 (December 2019) - Owodunni, Oluwafemi P.; Hampton, Jessica; Bettick, Dianne; Sateri, Sara; Magnuson, Thomas; Wick, Elizabeth; Psoter, Kevin J.; Gearhart, Susan L.
Abstract : Objective: This study was performed to evaluate compliance to an Enhanced Recovery Pathway (ERP) among patients ≥65 years and determine the effect of compliance on postoperative outcomes. Summary Background Data: ERPs improve postoperative outcomes in patients undergoing major surgery. Given the inherent decline of the older surgical patient, the benefit of an ERP in this population has been questioned. Methods: Patients undergoing major small and large intestinal surgery prior to and following ERP implementation at the Johns Hopkins Medical Institutions were entered into the ACS-NSQIP database. Outcomes included ERP compliance rates, complications, length of stay (LOS), and 30-day readmission rates were determined for older patients. Results: Nine hundred seventy-four patients (693 < 65 yrs and 281 ≥ 65 yrs) were included. Of those ≥ 65 years, 142 (51%) were entered prior to and 139 (49%) were entered following ERP implementation. More ERP than pre-ERP patients underwent laparoscopic procedures (45.3% vs. 32.4%, P = 0.02), had disseminated malignancies (9.4% vs. 2.8%, P = 0.03), and smoked (14.4% vs. 4.9%, P = 0.01). Overall compliance was 74.5%, and 47% of older ERP patients achieved high compliance (≥75% compliance with ERP variables). High compliance was associated with a 30% decrease LOS (IRR: 0.7 P = 0.001) and 60% decrease in major (CD ≥ II) complications (OR: 0.4 P = 0.05). Conclusion: LOS and complication rates following implementation of an ERP were significantly improved in highly compliant elderly patients. Interventions to further improve outcomes should target decreasing variability by increasing individual compliance with an effective clinical pathway.